Larrea tridentata (DC.) Coville Leaf Extracts Inhibit the Growth Gastrointestinal Bacterial Pathogens - Zyl, Rebecca Van; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Larrea tridentata (DC.) Coville leaves are used traditionally to treat diarrhoea and general bacterial infections. Despite the traditional uses, relatively few studies have examined the ability of L. tridentata leaf extracts to inhibit the growth of bacterial gastrointestinal pathogens. Materials and Methods: The growth inhibitory activity of L. tridentata leaf extracts was assessed against a panel of gastrointestinal bacterial pathogens by disc diffusion and liquid dilution minimum inhibitory concentration (MIC) methods. The toxicity of the extracts was evaluated by Artemia nauplii lethality assays. Results: Larrea tridentata extracts strongly inhibited the growth of several bacterial gastrointestinal pathogens, with MIC values as low as 86 μg/mL. The aqueous and chloroform extracts were particularly good inhibitors of several of the most virulent pathogens, although the methanolic and ethyl acetate extracts also displayed noteworthy activity against some pathogens. None of the L. tridentata extracts were toxic in the ALA toxicity assay, indicating that they are safe to use therapeutically. Conclusion: Larrea tridentata leaf extracts inhibited the growth of a panel of clinically relevant gastrointestinal pathogens. Thus, L. tridentata leaf extracts have potential in the treatment of diarrhoea and other gastrointestinal diseases.
Keywords: Chaparral; Creosote bush; Antibacterial activity; Gastrointestinal disease; Diarrhoea; Bacillus cereus; Shigella sonnei; Staphylococcus aureau.